Complementary Feeding Practices And Its Economic And Social Impact: A Cross Sectional Hospital Based Study - Bisoi, Swarup Kumar; Mohanty, Mamata Devi; Dash, Dillip Kumar; Giri, Satabdi (Journal of Nepal Paediatric Society, 2019)
Introduction: According to NHFS-4 data, around 38% of under-five Indian children are malnourished and stunted. In addition to poor socio-economic status, faulty complementary feeding practice is a major contributor to this. The objective of this study is to know the prevailing complementary feeding practices in our area, the most common food type preferred for introduction during initiation of complementary feeds, knowledge of the mother and their family members regarding complementary feeding, the factors influencing in decision making and its financial burden on the family. Methods: This hospital based cross-sectional study was conducted in a private Medical College in Bhubaneswar, Odisha, India. 256 mothers of infants between six months to two years attending Paediatric OPD from December 2018 to June 2019 were selected by random sampling technique. Data were collected using a structured questionnaire. Results: Out of the total 256 subjects interviewed, 134 (76.13%) out of 176 families belonging to lower income group preferred commercially available processed food over home food as the initial weaning food as compared to 32 (40%) out of 80 of the high income group preferring the same. The lower income group spent 22.3% of the total family income on commercial preparations to feed their infants in the age group six to 12 months. Whereas high income group families spend an average of 14.3% of family income on baby food products in the same age group. Despite being in regular contact with the local physician, in 85% of the total visits to the doctor, the opportunity wasn’t utilised to counsel the family member about complementary feeding practices. Conclusions: Commercial preparations are the primary preferred weaning food. The dietary diversity of complementary food is very poor, thus affecting growth and development. The false perception that commercial preparations are critical to child growth and development is overburdening the family finances.